Analysis of the contribution of machine learning to information security - Correa Wachter, Juan Fernando; Henao Villas, Cesar Felipe; Henao Villa, Federico; David Alberto, David Alberto; Correa Wachter, Juan Fernando; Henao Villas, Cesar Felipe; Henao Villa, Federico; García Arango, David Alberto; Correa Wachter, Juan Fernando; Henao Villas, Cesar Felipe; Henao Villa, Federico (Corporación universitaria Americana, 2021)
Every computing device has its own security logs. Byaggregating thousands of devices that intervene in thecommunications of personal computers, databases, webservers, network devices, firewalls, etc., a large volume oflogs is generated with interesting information from thesecurity point of view, although impossible to review by ahuman. That is where it has automated tools with a certainintelligence capable of performing analyzes and detectingmalicious patterns that can affect the confidentiality,integrity and availability of information.Among these tools arise Artificial Intelligence and MachineLearning, which are being included by manufacturers inthe latest generation security products. The objective ofthis article is to explain what Machine Learning consists of,its history, components and its contribution in support ofinformation security.